The exile's journey ebook - Hunter, Erin (Survivors: The Gathering Darkness, 2018)
A loyal dog must make her way alone in this gripping fifth book in the second Survivors series. From Erin Hunter, #1 nationally bestselling author of Warriors, Survivors is full of "wild and wonderful adventure" (Kirkus; starred review) that will thrill fans of Spirit Animals and Wings of Fire. Storm is in exile—and though she's finally free of the suspicion of her Packmates, she feels more lost than ever. There are only two dogs she knows will never give up on her: Arrow and his mate, Bella. To find them, Storm must fight through longpaw dangers, Leashed Dogs, and a forbidding pack of wolves, all in search of a place where she might finally belong.